Recent progress in surgical adhesives for biomedical applications - Kaikai Zheng; Qinhao Gu; Dong Zhou; Muran Zhou; Lei Zhang (Smart Materials in Medicine, 2022)
The increasing demands for the management of hemostasis and tissue sealing drive the development of novel bioadhesives, which can overcome the disadvantages of conventional sutures such as additional tissue damage, increased infection probability, and body fluid/air leakage. Bioadhesives can form a protective layer with seamless adhesion between the injured tissues, thereby quickly closing the wound and creating appropriate microenvironments for wound healing. In this review, the recent advancement in bioadhesives made of natural macromolecules (polysaccharides and proteins, etc.) and synthetic macromolecules (cyanoacrylate, polyethylene glycol, polyurethane, etc.) have been summarized. The gelation and adhesion mechanisms that determine the bioadhesive properties and sealing functions are highlighted, and the current clinical applications of bioadhesives are also discussed. Based on these findings, a brief outlook on the future of bioadhesive is explored.